Pengembangan Game Geomaze Berbasis Aplikasi Untuk Menstimulasi Kecerdasan Visual Spasial Anak Usia 4-5 Tahun - Aprilia Mardiani Dita Safitri (Publikasi Indonesia, 2022)
Early childhood is the initial stage of children in the process of growth and development to become mature in life later. By providing education from an early age, it is expected to be able to increase the growth and development of children in developing their abilities. This study aims to develop application-based geomaze games and determine the effectiveness of application-based geomaze games on visual-spatial intelligence of children aged 4-5 years. This research is an R&D (Research and Development) research using the ASSURE model. The data analysis technique in this study used descriptive statistical analysis techniques. This study uses target participants, namely children aged 4-5 years in TK Kusuma Bangsa as a test of the validity of the instrument and children aged 4-5 years at TK Dharma Wanita Persatuan 1 Gresik Regency as the main sample for testing the game product based on applications and conventional products ( LCA). The data collection tool in this study used a questionnaire from material experts and media experts, teachers and parents. The data obtained came from the collection of questionnaires carried out through the distribution of online google forms, in order to obtain product validation and obtain input for product improvement materials from experts as well as get feedback from parents on children's visual-spatial intelligence in order to get an overview of this intelligence and also test the effectiveness of the media. app based geomaze game. The results of this study indicate that the application-based geomaze game media is effective in increasing the visual-spatial intelligence of children aged 4-5 years. From the results of the feedback survey given by parents, it shows that the application-based geomaze game media that was developed effectively stimulates children's visual space intelligence in recognizing shapes and colors compared to traditional media using worksheets commonly used in schools which have proven to be effective learning media.